Non-linear tools and methodological concerns measuring human movement variability: an overview - Carla Caballero; David Barbado; Francisco Javier Moreno (Asociación Española de Ciencias del Deporte, 2014)
In recent years, several works have explored variability using different approaches, trying to describe the variations in motor movement. Traditionally, movement variability was regarded as a system error due to noise of neuromuscular mechanisms, but alternative theories suggest that motor variability seems to reflect a functional behaviour improving motor control and enhancing learning. Controversial results have been reported about variability characteristics and its role in motor control and learning, and several works suggest that the main difficulty lies in how to measure this variability. In this work, we have outlined the most used non-linear tools to assess human variability, their applications, advantages and disadvantages. We have also suggested different methods about how to achieve a multidimensional approximation to motor variability. Finally, we have called attention to some methodological issues frequently reported as important aspects to take into account when measuring human movement variability.